2012
DOI: 10.1136/annrheumdis-2011-201177
|View full text |Cite
|
Sign up to set email alerts
|

Associations of CTX-II with biochemical markers of bone turnover raise questions on its tissue origin: data from CHECK, a cohort study of early osteoarthritis

Abstract: The similarities between uCTX-II and bone markers could be attributable to a link between cartilage and bone metabolism through metabolic and biomechanical mechanisms. However, other cartilage markers were hardly associated with uCTX-II and did not show such evident associations with bone markers. uCTX-II has unique relations with bone markers as compared to other cartilage markers and might reflect bone rather than cartilage metabolism. More thorough molecular validation of uCTX-II is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 49 publications
7
39
2
Order By: Relevance
“…CTX-II is seen as a marker of articular cartilage degradation 26 , but is also suggested to be involved in calcified cartilage layer changes or even bone metabolism 27,28 . The rapid elevation seen after a joint bleed is in accordance with studies demonstrating release of CTX-II into synovial fluid within 1 week after joint injury in humans 29 and a rise in uCTX-II levels in two different canine OA models 30 .…”
Section: Discussionmentioning
confidence: 99%
“…CTX-II is seen as a marker of articular cartilage degradation 26 , but is also suggested to be involved in calcified cartilage layer changes or even bone metabolism 27,28 . The rapid elevation seen after a joint bleed is in accordance with studies demonstrating release of CTX-II into synovial fluid within 1 week after joint injury in humans 29 and a rise in uCTX-II levels in two different canine OA models 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we show that a high calcium meal sustains attenuation of the rise in CTX-I seen with exercise, with clear reductions in blood concentrations immediately and 40 min following a 90 min bout of cycling. Although CTX-II was originally proposed to be a marker of cartilage degradation (Christgau et al, 2001), recent evidence suggests it is more strongly correlated with other markers of bone resorption (van Spil et al, 2013) and it therefore might have been expected to mirror the movements of CTX-I. In contrast, CTX-II was not affected by the pre-exercise meal in our study, but was strongly correlated with PINP, a proposed marker of bone formation.…”
Section: Discussioncontrasting
confidence: 61%
“…These peptides are cleaved by osteoblasts and are therefore associated with bone resorption. Cross linked C-telopeptide of type II collagen (CTX-II) was originally proposed as a marker of cartilage degradation (Christgau et al, 2001), although a recent investigation by van Spil et al (2013) has shown CTX-II to correlate more strongly with other markers of bone resorption. Amino-terminal cross-linking telopeptides of type I collagen (NTX-I) has been used as a biomarker of bone resorption, measured either in urine or serum and decreases in response to anti-resorptive therapies in osteoporotic adults (Civitelli et al, 2009).…”
Section: The Interaction Between Participation In Elite Road Cycling mentioning
confidence: 99%
See 1 more Smart Citation
“…A study by van Spil and colleagues challenged the use of the uCTX-II level as a cartilage degradation biomarker using the database of the Cohort Hip and Cohort Knee (CHECK) study [van Spil et al 2013]. In this study, a long-term follow-up cohort of 1002 participants were included who were between 45 and 65 years of age at the time of inclusion with pain or stiffness of one or both knees or hips and who had never visited a general physician for these complaints, or had visited a general physician for the first time no longer than 6 months earlier.…”
Section: Unique Characteristics Of Uctx-iimentioning
confidence: 99%